Effect of early treatment with ivabradine combined with beta-blockers versus beta-blockers alone in patients hospitalised with heart failure and reduced left ventricular ejection fraction (ETHIC-AHF): A randomised study. (15th August 2016) - Hidalgo, Francisco J.; Anguita, Manuel; Castillo, Juan C.; Rodríguez, Sara; Pardo, Laura; Durán, Enrique; Sánchez, José J.; Ferreiro, Carlos; Pan, Manuel; Mesa, Dolores; Delgado, Mónica; Ruiz, Martín
Abstract: Objectives: To analyse the effect of the early coadministration of ivabradine and beta-blockers (intervention group) versus beta-blockers alone (control group) in patients hospitalised with heart failure and reduced left ventricular ejection fraction (HFrEF). Methods: A comparative, randomised study was performed to compare the treatment strategies of beta-blockers alone versus ivabradine and beta-blockers starting 24 hours after hospital admission, for acute HF in patients with an left ventricular ejection fraction (EF) < 40%, sinus rhythm, and a heart rate (HR) > 70 bpm. Results: A total of 71 patients were examined, 33 in the intervention group and 38 in the control group. No differences were observed with respect to their baseline characteristics or standard treatment at discharge. HR at 28 days (64.3 ± 7.5 vs. 70.3 ± 9.3 bpm, p = 0.01) and at 4 months (60.6 ± 7.5 vs. 67.8 ± 8 bpm, p = 0.004) after discharge were significantly lower in the intervention group. Significant differences were found with respect to the EF and brain natriuretic peptide levels at 4 months. No differences in clinical events (rehospitalisation/death) were reported at 4 months. No severe side effects attributable to the early administration of ivabradine were observed. Conclusions: The early coadministration of ivabradine and beta-blockers during hospital admission for acute HFrEF is feasible and safe, and it produces a significant decrease in HR at 28 days and at 4 months after hospital discharge. It also seemed to improve systolic function and functional and clinical parameters of HF patients at short-term.